2003
DOI: 10.1097/00042752-200307000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human β-Enolase as a Serum Marker for Exercise-induced Muscle Damage

Abstract: Our data suggest that the absolute values of the serum beta-enolase are more appropriate to relate to muscle damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In a recent proteomics study, enolase 1 alpha and proteins similar to alpha enolase have been found to increase in exercised rats [36]. Moreover, beta enolase was observed to increase in athletes after running a race [37]. These data further indicate an important role of beta enolase in the preconditioning phenomena that induce cardioprotection.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent proteomics study, enolase 1 alpha and proteins similar to alpha enolase have been found to increase in exercised rats [36]. Moreover, beta enolase was observed to increase in athletes after running a race [37]. These data further indicate an important role of beta enolase in the preconditioning phenomena that induce cardioprotection.…”
Section: Discussionmentioning
confidence: 95%
“…Phosphoglycerate kinase, triosephosphate isomerase, and muscle specific glycolytic enzyme beta-enolase play important roles in glycolysis and glucogenesis and are essential for efficient energy production. Beta- enolase is also known as a serum marker for muscle damage22.…”
Section: Resultsmentioning
confidence: 99%
“…Beta enolase is a glycolytic enzyme of particular interest because it has muscle specifi c isoforms (Chosa E et al 2003). In adults, subunits of the muscle isoform of enolase (b-enolase) accumulate preferentially in fast-twitch muscle fi bers in which the b-isoenzyme accounts for more than 90% of total enolase.…”
Section: Discussionmentioning
confidence: 99%